2018
DOI: 10.1016/j.molcel.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, Structure, and Context Preferences of Human RNA Binding Proteins

Abstract: RNA binding proteins (RBPs) orchestrate the production, processing, and function of mRNAs. Here, we present the affinity landscapes of 78 human RBPs using an unbiased assay that determines the sequence, structure, and context preferences of these proteins in vitro by deep sequencing of bound RNAs. These data enable construction of "RNA maps" of RBP activity without requiring crosslinking-based assays. We found an unexpectedly low diversity of RNA motifs, implying frequent convergence of binding specificity tow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
378
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 452 publications
(402 citation statements)
references
References 67 publications
22
378
1
1
Order By: Relevance
“…Canonical RBDs include, among others, RNA recognition motifs (RRM), heterogeneous ribonucleoprotein (hnRNP) K‐homology (KH) domains, zinc‐finger (ZF) domains, cold‐shock domains (CSD), DEAD‐box domains, and double‐stranded RNA‐binding motifs (dsRM). The characterization of human RBPs harboring RRM, KH, and ZF domains revealed that canonical RBDs preferentially bind a subset of RNA sequences composed of one or two bases that are unable to form secondary structures that might block RBP binding . Thus, accessibility differences may have guided the evolution of RBP specificity toward a subset of attainable motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Canonical RBDs include, among others, RNA recognition motifs (RRM), heterogeneous ribonucleoprotein (hnRNP) K‐homology (KH) domains, zinc‐finger (ZF) domains, cold‐shock domains (CSD), DEAD‐box domains, and double‐stranded RNA‐binding motifs (dsRM). The characterization of human RBPs harboring RRM, KH, and ZF domains revealed that canonical RBDs preferentially bind a subset of RNA sequences composed of one or two bases that are unable to form secondary structures that might block RBP binding . Thus, accessibility differences may have guided the evolution of RBP specificity toward a subset of attainable motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Of this total, the concentration of GCAUG will fall between ~16 to 63 nM, with GCACG fivefold lower (3-12 nM), and the four secondary motifs together occurring at severalfold higher concentration (67 to 270 nM) ( Supplementary Figure 10a). After assigning approximate dissociation constants to all Rbfox 5mer motif variants by calibrating our random RBNS data for human RBFOX2 and RBFOX3 26 to SPR data 29 ( Supplementary Figure 9, Supplementary Table 3), we modeled the equilibrium distribution of Rbfox proteins across the pool of nuclear binding sites, analogous to a previous model for miRNAs 44 .…”
Section: A Quantitative Model For Rbfox Expression-dependent Differementioning
confidence: 99%
“…Although Rbfox binding to canonical GCAUG motifs and rarer GCACG motifs is well characterized, studies of Rbfox binding sites in vivo using crosslinkingimmunoprecipitation (CLIP) have observed that about half of CLIP peaks lack an associated GCAYG (Y = C or U) motif 23 , suggesting the existence of additional binding determinants 26 . Indeed, recent work has observed GUGUG motifs and motifs differing by one base from the canonical GCAUG in CLIP peaks 12,[27][28][29] , and RBFOX1 was shown to compete with MBNL1 at a GCCUG motif 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Many novel functions for mRNPs have been identified from these studies, and numerous insights into the constitution and biophysical properties of mRNP binding sites were also uncovered. An important discovery from these studies (along with independently performed crystallographic analyses) is that many mRNPs make extensive use of RNA secondary structure in binding to mRNA elements (Dominguez et al, 2018). This frequently includes making multiple contacts with the phosphate backbone and other non-nucleotidespecific interactions (Schlundt et al, 2014).…”
Section: Commentary Background Informationmentioning
confidence: 99%